The neuropsychological assessment battery (NAB) is a valuable tool for evaluating neuropsychological outcome after aneurysmatic subarachnoid hemorrhage - Walter, Johannes; Grutza, Martin; Vogt, Lidia; Unterberg, Andreas; Zweckberger, Klaus (BMC neurology, 2020)
Detecting and treating neuropsychological deficits after aneurysmatic subarachnoid hemorrhage (aSAH) play a key role in regaining independence; however, detecting deficits relevant to social and professional reintegration has been difficult and optimal timing of assessments remains unclear. Therefore, we evaluated the feasibility of administering the Neuropsychological Assessment Battery screening module (NAB-S) to patients with aSAH, assessed its value in predicting the ability to return to work and characterized clinical as well as neuropsychological recovery over the period of 24 months.